2018
DOI: 10.1186/s13071-018-3105-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasite infections and associated risk factors among schoolchildren in Dolakha and Ramechhap districts, Nepal: a cross-sectional study

Abstract: BackgroundInfections with soil-transmitted helminths and pathogenic intestinal protozoa pose a considerable public health burden, particularly in low- and middle-income countries, including Nepal. We assessed the extent of intestinal parasite infections among schoolchildren in two districts of Nepal and determined underlying risk factors.MethodsA cross-sectional survey was conducted between March and May 2015 in the districts of Dolakha and Ramechhap, Nepal. A total of 708 children, aged 8–16 years from 16 pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 38 publications
(72 reference statements)
2
15
2
1
Order By: Relevance
“…Intestinal protozoa infections (B. hominis, E. histolytica, E. coli and intestinal flagellates were prevalent than soil-transmitted helminth infection (A. lumbricoides, S. stercoralis, hookworm and S. mansoni). This finding is in contrast with the findings of a study conducted in Nepal [16] and Saudi Arabia [17] which revealed soil-transmitted helminth as the most predominant intestinal parasite. The low prevalence of soil-transmitted helminth infection in this study could be due to the periodic deworming exercise initiated by the regional School Health and Education Programme (SHEP) of Ghana Education Service / Ministry of Education and the Neglected Tropical Disease Control Programme (NTDCP) of the Ghana Health Service [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Intestinal protozoa infections (B. hominis, E. histolytica, E. coli and intestinal flagellates were prevalent than soil-transmitted helminth infection (A. lumbricoides, S. stercoralis, hookworm and S. mansoni). This finding is in contrast with the findings of a study conducted in Nepal [16] and Saudi Arabia [17] which revealed soil-transmitted helminth as the most predominant intestinal parasite. The low prevalence of soil-transmitted helminth infection in this study could be due to the periodic deworming exercise initiated by the regional School Health and Education Programme (SHEP) of Ghana Education Service / Ministry of Education and the Neglected Tropical Disease Control Programme (NTDCP) of the Ghana Health Service [18].…”
Section: Discussioncontrasting
confidence: 99%
“…This study attempted to determine some potential risk factors associated with the prevalence of parasitosis among school going children of two schools based in Saptari district. In this study, one third of enrolled school children (33%, 94/285) was found to be infected with intestinal parasites and a similar rate of prevalence was reported by Shah et al [17] while some other studies have reported a low rate of intestinal parasites in school going children from different parts of the country [6,18,19]. Higher prevalence of IPIs in the study might be due to the contamination of the drinking water supply by the parasites and poor sanitation practice in the study sites [20].…”
Section: Discussionsupporting
confidence: 87%
“…Higher prevalence of IPIs in the study might be due to the contamination of the drinking water supply by the parasites and poor sanitation practice in the study sites [ 20 ]. On the other hand, Shreshtha et al have reported 39.7% of IPIs among school children of two schools from central Nepal [ 18 ]. Similarly, very high rates of IPIs were reported in school children from different countries [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de Giardia em populações infantis estimadas na faixa de 3-35% em diferentes ambientes e regiões da comunidade 8,9,10 . No entanto, esses achados são limitados devido ao pequeno tamanho das amostras.…”
Section: Introductionunclassified